The Garfield movie [videorecording (Blu-Ray + DVD)] - Kaplan, Paul A.; Torgove, Mark; Reynolds, David (Dave); Debney, John (Columbia Pictures, Sony Pictures Home Entertainment, 2024)
Garfield, the world-famous, Monday-hating, lasagna-loving indoor cat, is about to have a wild outdoor adventure! After an unexpected reunion with his long-lost father scruffy street cat Vic Garfield and his canine friend Odie are forced from their perfectly pampered life into joining Vic in a hilarious, high-stakes heist.